2009
DOI: 10.28945/3341
|View full text |Cite
|
Sign up to set email alerts
|

E-portfolio Assessment System for an Outcome-Based Information Technology Curriculum

Abstract: Currently colleges and universities are facing a number of problems, including ill designed curricula that do not address demands from the job market. There is also tremendous pressure from society on academic institutions to provide an education that results in guaranteed employment, especially given the soaring price of higher education. Currently, a number of academic institutions are facing the problem of grade inflation, which has resulted in the grade point average (GPA) model losing its value (Mansfield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…EPortfolios can be designed to meet course learning outcomes, which in turn are aligned with program outcomes and typically aim to address both institutional effectiveness requirements, and program accreditation requirements (Tubaishat, Lansari & Al-Rawi, 2009). …”
Section: Assessment and Accountabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…EPortfolios can be designed to meet course learning outcomes, which in turn are aligned with program outcomes and typically aim to address both institutional effectiveness requirements, and program accreditation requirements (Tubaishat, Lansari & Al-Rawi, 2009). …”
Section: Assessment and Accountabilitymentioning
confidence: 99%
“…Universities are feeling pressure from the public to be relevant and provide a curriculum that prepares students to enter a challenging job market (Tubaishat et al, 2009). Employers expect college graduates to be prepared and have readiness for essential work tasks.…”
Section: Career Connectionsmentioning
confidence: 99%
“…ePortfolios have been linked to self-regulated learning (SRL) in HE, and it has been suggested that ePortfolios can promote SRL (Blackburn & Hakel, 2006;Cheng & Chau, 2013). A shift to outcomesbased education will require tools that demonstrate and track such learning (Tubaishat, Lansari, & Al-Rawi, 2009).…”
Section: Eportfolios In Programs Preparing Students For Professional mentioning
confidence: 99%
“…However, researchers find fault with adapting higher education to the needs of the consumer and claim that the knowledgeas-consumer-goods approach mightassign lesser importance to theoretical knowledge per se, and instead base its academic curricula on the professional demands of employers and emphasize professional and personal skills instead (Velde, 2009;Tubaishat, Lansari, & Al-Rawi, 2009;Meleki, 2009). These adaptations to the needs of the market place can impinge on other professional requirements, such as the need of professionals to acquire broad knowledge bases in their fields (Heckman & Montera, 2001).…”
Section: The Perception Of Knowledge As Consumer Goodsmentioning
confidence: 99%